Taxonomy of ants subfamily formicinae (hymenoptera: formicidae) from Universiti Teknologi MARA (UiTM) Cawangan Pahang, Kampus Jengka. / Siti Norlela Abd Wahab - Abd Wahab, Siti Norlela (Faculty of Applied Sciences, 2017)
This study is about collecting the ants that categorized under the family of Formicidae. But, it only focused on identifying the species under one subfamily which is Formicinae that exist in UiTM Pahang. The problem statements of this research were the total number of ants species that live in UiTM Pahang is not accurately known, the morphology and characteristics of the species is not well documented and existence of species distribution of ants with differing population is unidentified. The goals of this study is to identify the species under subfamily Formicinae. Next, to study the dichotomous key and describe the morphology and characteristics of the species. Last objective is to map the existing species of subfamily Formicinae in UiTM Pahang. The sampling time for this research is from September until October. There are two sampling methods which were pitfall trap and the Winkler method. The samples were observed under the microscope in order to identify the taxonomic characteristic. An identification key and morphology description based on the species, genus and family were provided. The sampling area consists of plantation, residential and forest reserve. The results obtained were 229 individuals of the ants subfamily Formicinae. This comprises of 9 genera and 23 species. The most common genera recorded were Polyrhachis followed by Camponotus. The rare genera which were Formica and Lepisiota and Camponotus gigas was the rare species. Plantation yields the highest number of genera and species which 9 genera and 22 species, followed by 8 genera and 21 species from forest reserve and 9 genera and 20 species from residential.